2016
DOI: 10.1179/1351000215y.0000000028
|View full text |Cite
|
Sign up to set email alerts
|

Time courses of changes ofpara-,meta-, andortho-tyrosine in septic patients: A pilot study

Abstract: Our data suggest that the oxidative stress marker m-Tyr and physiologic p-Tyr may be handled differently in septic patients. The excretion of m-Tyr correlates with inflammation. m-Tyr may be actively secreted or produced in the kidney in some patients, whereas the decreased serum level of p-Tyr is a consequence of diminished renal production and not of renal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…While the renal excretion of p -tyrosine does not significantly differ in these disease states compared to healthy controls (median FE in CKD = 1.36%; in diabetes = 0.98%; in CKD and diabetes = 1.06%), there is a marked increase in the renal excretion of o -tyrosine in patients with these diseases (median FE in CKD = 27.28%; in diabetes = 125.29%; in CKD and diabetes = 111.89%); although it should be noted that in patients with chronic kidney disease alone these values failed to reach significance (Molnar et al, 2005b). Recently similar results were also reported in septic patients with the fractional excretion of m -tyrosine (mean FE = 61.0%) and o -tyrosine (mean FE = 243%) being significantly greater than that of p -tyrosine (mean FE = 1.6%) (Szelig et al, 2015). It is, however, unclear whether these results represent an adaptation of the kidneys to preferentially clear m - and o -tyrosine under conditions that are potentially favorable for the production of the abnormal tyrosine isomers, a reflection of some aspect of kidney damage in these diseases, or whether this could represent in loco production of the abnormal tyrosine isomers within the kidney during diseased states.…”
Section: How Could Tyrosine Isomers Contribute To the Adverse Effesupporting
confidence: 73%
“…While the renal excretion of p -tyrosine does not significantly differ in these disease states compared to healthy controls (median FE in CKD = 1.36%; in diabetes = 0.98%; in CKD and diabetes = 1.06%), there is a marked increase in the renal excretion of o -tyrosine in patients with these diseases (median FE in CKD = 27.28%; in diabetes = 125.29%; in CKD and diabetes = 111.89%); although it should be noted that in patients with chronic kidney disease alone these values failed to reach significance (Molnar et al, 2005b). Recently similar results were also reported in septic patients with the fractional excretion of m -tyrosine (mean FE = 61.0%) and o -tyrosine (mean FE = 243%) being significantly greater than that of p -tyrosine (mean FE = 1.6%) (Szelig et al, 2015). It is, however, unclear whether these results represent an adaptation of the kidneys to preferentially clear m - and o -tyrosine under conditions that are potentially favorable for the production of the abnormal tyrosine isomers, a reflection of some aspect of kidney damage in these diseases, or whether this could represent in loco production of the abnormal tyrosine isomers within the kidney during diseased states.…”
Section: How Could Tyrosine Isomers Contribute To the Adverse Effesupporting
confidence: 73%
“…Supporting these data, a study in patients with sepsis found that changes in inflammatory markers (CRP and procalcitonin - PCT) were paralleled by changes in serum levels of m-Tyr and urinary excretion of both m- and o-Tyr [ 53 ].…”
Section: Acute Diseases Associated With Oxidative Stressmentioning
confidence: 95%
“…However, p-Tyr could more effectively overcome the inhibition by o-Tyr than by m-Tyr [ 78 ]. In the study on septic patients, serum levels of m-Tyr seemed at least as high as that of o-Tyr, however, urinary concentration and fractional excretion of o-Tyr was markedly higher than that of m-Tyr in the patients [ 53 ]. In the study on glycemia in septic patients, serum m- and o-Tyr levels were identical, however urinary concentration, daily excretion, clearance and fractional excretion of o-Tyr were approx.…”
Section: Relative Abundance Of Tyrosine Isomers and Their Significancmentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay between malignant cells and surrounding stromal cells is a milestone for understanding the role of microenvironment in tumor progression [ 108 ]. In this context, an active network is regulated by signals driven by cytokines, chemokines, growth factors, inflammatory cells, immune cells and enzymes involved in stroma remodeling [ 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ].…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%